A comprehensive two-dimensional numerical study on unsteady conjugate heat transfer in magnetic refrigerator with Gd plates. (July 2017) - You, Yonghua; Wu, Zhongda; Xiao, Shuifang; Li, Hao; Xu, Xuecheng
Highlights: 2D comprehensive numerical model is built with Fluent for magnetic refrigerator. Current numerical results match well with experimental data in the literature. Temperature span in the case of narrow channels varies convexly with cycling period. Channel width of 0.2 mm generates temperature span of 12.25 K at cycling period of 2 s. Abstract: In the present work, the comprehensive two-dimensional numerical model is constructed with ANSYS Fluent for the unsteady conjugate heat transfer of magnetic refrigerator with Gd plates. To express the reciprocating piston movements and magneto-caloric effect, etc., several user-defined functions are compiled. With current model, the reciprocating magnetic refrigerator in the literature is simulated under room temperature conditions and its refrigeration mechanism is analyzed. Besides, the effect of cycling period (τ) on maximal temperature span (ΔTmax ) is numerically investigated and different channel widths (w) are adopted for the effects of heat transfer enhancement. Computation results indicate that current comprehensive model could match well with public experimental data and the ΔTmax is effectively improved with smaller w at the cost of substantial increase of pressure difference. Moreover, the ΔTmax generated by narrower channels varies convexly with the τ, and the peak ΔTmax increases with a decreasing w.